2016
DOI: 10.1088/0957-4484/27/33/335202
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the electrical properties of silver nanowire transparent conductive electrodes by atomic layer deposition coating with zinc oxide

Abstract: Transparent conductive electrodes for applications in optoelectronic devices such as solar cells and light-emitting diodes are important components and require low sheet resistance and high transmittance. Herein, we report an enhancement of the electrical properties of silver (Ag) nanowire networks by coating with zinc oxide using the atomic layer deposition technique. A strong decrease in the sheet resistance of Ag nanowires, namely from 20-40 Ω/□ to 7-15 Ω/□, was observed after coating with ZnO. Ag nanowire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Doctor blade coating is a simple process that uses a well-dispersed and homogenous nanomaterial ink with suitable solvent, binder and dispersants [169][170][171]. The film thickness depends on the distance between the blade and substrate, while the surface morphology depends on the density of ink and blade speed [172].…”
Section: Doctor Blade Coatingmentioning
confidence: 99%
“…Doctor blade coating is a simple process that uses a well-dispersed and homogenous nanomaterial ink with suitable solvent, binder and dispersants [169][170][171]. The film thickness depends on the distance between the blade and substrate, while the surface morphology depends on the density of ink and blade speed [172].…”
Section: Doctor Blade Coatingmentioning
confidence: 99%
“…Yeh et al [74] and Ma et al [75] applied the ALD technique to coat AgNWs and AgNRs respectively with a highly uniform and conformal TiO 2 layer to improve their stability. Chen et al 76], Pham et al [77] and Duan et al [78] reported an enhancement of the AgNWs performance by coating with zinc oxide (ZnO) using the ALD technique. Yang et al [79], Ma et al [80], Fedel et al [81], Ali et al [82], David et al [83], Guay et al [84] and Park et al [85] evaluated the effectiveness of alumina (Al 2 O 3 ) fabricated by ALD as a protective coating for Ag articles against the corrosion.…”
Section: Magnetron Sputtering (Msmentioning
confidence: 99%
“…[8] Various materials have been studied to passivate silver nanowires. [11][12][13][14][15][16][17] Typically nanowires on a substrate can be encapsulated within a film of organic or inorganic material such as metal oxide (Al 2 O 3 , ZnO, TiO 2 ), graphene or polymers. [11][12][13][14] However, these matrices affect the intrinsic properties of the nanowire film.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Typically nanowires on a substrate can be encapsulated within a film of organic or inorganic material such as metal oxide (Al 2 O 3 , ZnO, TiO 2 ), graphene or polymers. [11][12][13][14] However, these matrices affect the intrinsic properties of the nanowire film. Passivating the nanowire surface only, rather than blanketing the nanowires in a film, is a promising alternative strategy as it should not, for example, lower the transparency of a nanowire film or interfere with its mechanical flexibility.…”
Section: Introductionmentioning
confidence: 99%